Mechanism of Dispersion of Non-Polar Collecting Reagents in Coal Slime Flotation - Samoilov, Anatolii; Biletskyi, V. S.; Desna, N. A. (VÚRUP, 2025)
The article investigates the conditions under which non-polar reagents interact with coal slimes during the enrichment process. This is important for determining the mechanism of their dispersion in turbulent flows in the presence of a solid phase. The study analyses and summarizes contemporary scientific research on coal flotation and the dispersion of non-polar reagents. Specifically, it addresses the particle size distribution of coal slime and analyses collector dispersion conditions. Theoretical calculations were made regarding the elementary act of dispersing particle complexes connected by the reagent. The findings indicate that pre-emulsifying non-polar reagents to sizes larger than 3 μm helps achieve a uniform distribution of the collector throughout the pulp. However, it does not provide sufficient treatment of coal particles before flotation. The research shows that, in real-world conditions, the distance between solid phase particles is smaller than their average size. The proposed mechanism for dispersing reagent includes the formation of “particle-reagent” and “particle-reagent-particle” complexes and their breakdown in turbulent pulp flows, allowing the collector particle to adhere to the oleophilic surface of the particle due to strong mutual adhesion. Additionally, a method for calculating the parameters of spherical particle complexes bonded by a non-polar phase under equilibrium conditions has been developed. Theoretical possibilities for dispersing reagents into nanoscale volumes during the formation and breakdown of complexes have been demonstrated. The practical implications of these results suggest ways to improve coal slime processing with collecting reagents without using surfactants or specialized equipment, based on the proposed dispersion mechanism. Using the developed methodology, the study has found that for more oleophilic particles, the forces required to break particle complexes bonded by the reagent will be 1.8 to 2.2 times lower within the investigated range of contact angles of the solid phase with the collector of 125º to 145º. Lastly, it highlights the impact of particle size ratios on dispersion results during the breakdown of complexes, showing that increasing the “contact/break” interactions reduces the volume of the pre-attached reagent in a geometric progression.
Keywords: flotation; coal slime; non-polar reagent; drop size; dispersion mechanism